12-month trajectories of depressive symptoms among nurses—Contribution of personality, job characteristics, coping, and burnout - Duan-Porter, Wei (J Affect Disord, 2018)
BACKGROUND: Job related factors have been associated with higher risk for developing depression, but past studies lacked full consideration of individual factors such as personality and coping. We sought to evaluate associations of personality, coping, job characteristics, and burnout with 12-month trajectories of depressive symptoms among nursing workers. METHODS: Cohort of nursing workers (N = 281) in a private hospital system, with baseline assessments of personality, job characteristics, and coping. Burnout and depression were measured at baseline and during monthly follow-ups. Linear mixed modeling was used to examine contributions to between- and within-individual variation in monthly depressive symptoms. RESULTS: Personality trait of negative affectivity accounted for 36% of between-individual variation in depressive symptoms over 12 months, while job characteristics and coping explained an additional 5% and 8% of this variation, respectively. Exhaustion dimension of burnout was associated with between-individual variation in depressive symptoms (fixed effect β coefficient 2.44, p < 0.001), but not with within-individual variation in symptoms. Disengagement dimension of burnout was not associated with between-individual variation in depressive symptoms, but contributed to within-individual variation in depressive symptoms over time (fixed effect β coefficient 0.52, p = 0.01). LIMITATIONS: Participants were nursing workers within a single hospital system. Participants who were excluded due to missing baseline data were more likely of non-white race, which may also limit the generalizability of our results. We used latent variables to represent certain job and coping characteristics, which may make our results less comparable with other studies examining the role of these factors in work-associated depression. CONCLUSIONS: Future interventions to prevent depression in healthcare workers should consider multiple job and individual factors. Potential components include strategies to manage negative affectivity and reduce avoidant coping, such as cognitive reframing and mindfulness-based techniques, and organizational approaches to address burnout through augmentation of job resources.